Healthy aging in India: evidence from a panel study - C.V. Irshad; Umakant Dash (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - Recent public health policy emphasizes the achievement of healthy aging as average life expectancy increases worldwide. Evidence for healthy aging from low- and middle-income countries (LMIC) is limited. The purpose of this paper is to assess the prospects of healthy aging and its associated factors in the Indian context. Design/methodology/approach - The study was based on a national-level panel survey, the Indian Human Development Survey (IHDS) conducted in 2004-05 and 2011-12. The analytical sample consists of 10,218 elderly individuals who were 60 years old and above at the baseline. Change in health status was assessed based on disability and disease incidence at the follow-up. A generalized estimating equation (GEE) model was performed to assess health status change. Findings - Increasing age was a risk factor for all dimensions of health outcomes. Elderly from the lowest wealth quintiles were more likely to lose health due to short-term morbidity, whereas the highest wealth quintiles were more likely to lose health due to long-term and multi-morbidity, indicating evidence for the presence of the "disease of affluence". Social capital, such as living in a joint family acted as a protective factor against health risks. Originality/value - With the results showing the evidence of the "disease of affluence" and "disease of poverty" in different health outcomes, there should be a health policy focus that copes with undergoing epidemiological transition. It is also important to pay attention to health-protecting factors such as social and familial support to achieve healthy aging.